Supercapacitors from Reduced Graphene Oxide Material - Maryati Doloksaribu; Makmur Sirait; Erniwati Halawa; Mukti Hamjah Harahap (Jurnal Penelitian Pendidikan IPA, 2025)
Reduced graphene oxide (rGO) has been chemically synthesized from graphite powder. Graphite powder is oxidized using a strong oxidizing compound to obtain graphite oxide, this process is called the Hummer Method. Graphite oxide is dispersed using an ultrasonic vibrator to peel off the graphite oxide layer and become graphene oxide. The epoxy group in graphite oxide is reduced using 80 wt% hydrazine compound at temperatures of 70????, 80 and 90????C to obtain reduced graphene oxide. Then rGO is characterized using Uv-Vis spectroscopy, and FTIR. The Uv-Vis spectrum shows that the absorbance of rGO decreases with increasing reduction temperature. Then the absorbance data is calculated for its optical constant using the Kramers-Kronig Method. The refractive index values ​​of the real and imaginary parts of the calculation results show that in the low energy region an increase in the optical constant value is obtained with the addition of rGO. Then rGO was used in supercapacitor fabrication using PVA as a binder, 1 M ????2????????4 electrolyte, and aluminum foil as a collector and the supercapacitor mass was obtained as much as 0.01 grams. From the cyclic voltammetry measurement, the capacitor capacitance value was obtained as much as 24.5 F/gr.